ANALISIS BIAYA PRODUKSI UNTUK PRODUK BOTOL PLASTIK PADA INDUSTRI MANUFAKTUR - yevita nursyanti (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
Cost of Goods Sold (COGS) is a method for calculating all direct and indirect costs incurred for the production process as financial statements on sales results. This study aims to minimize costs when going to carry out production process activities. This analysis model uses the full costing method by calculating all costs incurred in the production process of plastic bottles, which in this full costing method takes into account all production costs, such as direct raw material costs, direct labor, variable overhead costs and fixed overhead costs. By using the cost of goods sold calculation method both the full costing method and variable costing can help management determine the selling price of the product in the sales process. The result of total production cost calculation using the full costing method is Rp 1,889,682,559 with total sales of 15,000,000 units multiplied by the selling price per bottle of Rp 150.00 then the selling price of Rp 2,250,000,000.00. The profit after tax was IDR 249,084,826.69 obtained from the sale of plastic bottles.